Differences in the prevalence of intermediate hyperglycaemia and the associated incidence of type 2 diabetes mellitus by ethnicity: The HELIUS study - van Olden, C.C.; Muilwijk, M.; Stronks, K.; van den Born, B.J.; Moll van Charante, E.P.; Nicolau, M.; Zwinderma, A.H.; Nieuwdorp, M.; Groen, A.K.; van Valkengoed, I.G.M. (Diabetes research and clinical practice, 2022)
We aimed to describe differences in the prevalence of intermediate hyperglycaemia (IH) between six ethnic groups. Moreover, to investigate differences in the association of the classifications of IH with the incidence of T2DM between ethnic groups. We included 3759 Dutch, 2826 African Surinamese, 1646 Ghanaian, 2571 Turkish, 2691 Moroccan and 1970 South Asian Surinamese origin participants of the HELIUS study. IH was measured by fasting plasma glucose (FPG) and HbA1c. We calculated age-, BMI and physical-activity-adjusted prevalence of IH by sex, and calculated age and sex-adjusted hazard ratios (HR)for the association between IH and T2DM in each ethnic group. The prevalence of IH was higher among ethnic minority groups (68.6–41.7%) than the Dutch majority (34.9%). The prevalence of IH categories varied across subgroups. Combined increased FPG and HbA1c was most prevalent in South-Asian Surinamese men (27.6%, 95 %CI: 24.5–30.9%), and in Dutch women (4.2%, 95 %CI: 3.4–5.1%). The HRs for T2DM for each IH-classification did not differ significantly between ethnic groups. HRs were highest for the combined classification, e.g., HR = 8.1, 95 %CI: 2.5–26.6 in the Dutch. We found a higher prevalence of IH in ethnic minority versus majority groups, but did not find evidence for a differential association of IH with incident T2DM.